The Trace Fossil Polykampton cabellae isp. nov. from the Pagliaro Formation (Paleocene), Northern Apennines, Italy: A Record of Nutritional Sediment Sequestration by a Deep Sea Invertebrate. Issue 1 (2nd January 2018) - Uchman, Alfred; Rattazzi, Bruno
ABSTRACT: Polykampton cabellae isp. nov., a new ichnospecies of Polykampton Ooster, 1869, occurs in two localities of the Pagliaro Formation (Paleocene) in Liguria, Italy, 1.5–3.5 cm below the top of light grey or rose, thick-bedded turbiditic marlstones, which are capped by a thin layer of dark grey, non-calcareous mudstones being the background sediments. This is a ribbon-like, winding, rarely branched trace fossil that consists of 1) a passively-filled axial tunnel and 2) complex, partly imbricated, side lobes, which are composed mostly of dark grey mudstones, the same as in the background sediments. The lobes are produced by multiple probing. The producer, supposedly a polychaete, collected organic-rich, nutritional mud from the sea-floor surface, packed it in a deeper layer in the organic-poor marl, and reworked for feeding. This enabled a stable feeding during longer times of fluctuating supply of organic matter to the sea floor.